2009
DOI: 10.1051/forest/2009080
|View full text |Cite
|
Sign up to set email alerts
|

Climate-growth variability in Quercus ilex L. west Iberian open woodlands of different stand density

Abstract: Abstract• We present the longest tree-ring chronology (141 y) of Quercus ilex L. (holm oak), and discuss the species climate-growth relationships and the influence of stand density on tree sensitivity to climate.• Similarly to Quercus suber L., the most influential climatic variables upon holm oak growth were late spring and early summer precipitation, which enhanced growth, and high temperatures in the previous August and current July, which negatively affected growth.• High density stands responded to simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 46 publications
(70 reference statements)
11
69
2
1
Order By: Relevance
“…Using a contrasted approach, Gea-Izquierdo et al (2009) and Piutti and Cescatti (1997) also Thinning affects growth response to climate in cedarhighlighted differences in the correlation between climate variables and annual growth among trees experiencing different competition intensities. Both studies reported a greater effect of water deficit (low precipitation and high temperatures) in denser stands.…”
Section: Effect Of Thinning On the Climate-growth Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a contrasted approach, Gea-Izquierdo et al (2009) and Piutti and Cescatti (1997) also Thinning affects growth response to climate in cedarhighlighted differences in the correlation between climate variables and annual growth among trees experiencing different competition intensities. Both studies reported a greater effect of water deficit (low precipitation and high temperatures) in denser stands.…”
Section: Effect Of Thinning On the Climate-growth Relationshipmentioning
confidence: 99%
“…The effect of competition intensity on the climate-growth relationship was often based on experiments that did not reproduce actual silvicultural guidelines: studies were conducted in stands that had not been thinned for decades (Gea-Izquierdo et al 2009;Martínez-Vilalta et al 2012), in stands thinned once (Misson et al 2003) and in stands lightly thinned (Piutti and Cescatti 1997;Timbal 2002;Kohler et al 2010; but see Olivar et al 2013 andSohn et al 2013). As a consequence, several important aspects of management impact on forest functioning were overlooked: (i) the short-and medium-term effects of thinning, (ii) the cumulative effect of successive thinning and (iii) the prospective analysis of the effect of thinning intensities beyond the current guidelines.…”
mentioning
confidence: 99%
“…ilex has become well-established especially in recent times (Zhang and Romane, 1991;Cherubini et al, 2003;Campelo et al, 2009;Gea-Izquierdo et al, 2009, 2011. These studies have demonstrated that Q. ilex ring formation is very sensitive to climate, indicating the suitability of this species for dendroecological investigations.…”
Section: Establishedmentioning
confidence: 98%
“…Complete cross-sections are needed for dendrochronological analysis of Q. ilex due to the complex xylem anatomy of this species (narrow rings, missing rings, and intra-annual density fluctuations [Cherubini et al, 2003;Campelo et al, 2007Campelo et al, , 2009Gea-Izquierdo et al 2009]). Previous dendroecological studies on tree mortality in Iberian forests included tree ring data from dead and healthy trees for comparative analyses (e.g.…”
Section: Sampling and Dendrochronological Analysesmentioning
confidence: 99%
See 1 more Smart Citation